DESIGN COMPARISON OF DRY BULK PORT BASED ON OCDI AND BS STANDARD IN CIREBON - PUTERA SATRIA, ALBANY
The steam power plant (PLTU) unit 2 in Cirebon is planned to be completed by 2020. The plant relies on coal as an energy source. The construction of this steam power plant will certainly increase the need for coal, therefore it needs a new unloading port of coal. In the construction of coal dock, of course need technical or standard regulations to regulate the design criteria of the dock. In Indonesia, the technical regulations or standards that are often used in designing the dock are the Overseas Coastal Development Institute of Japan (OCDI) and British Standard (BS). This Final Project will compare the dock design with OCDI standards and BS standards. Environmental data and operational data is required in designing the dock. Environmental data may be wind, tidal, wave, and soil data of location .Operational data can be plan ships, and operational tools on the dock. This environmental data and operational data are used as the basis for the design of the dock dimension, dock geometry and loading carried out by 2 technical or standard regulations namely Overseas Coastal Development Institute of Japan (OCDI) and British Standard (BS). The design results of the dock structure will then be analyzed using SAP2000 software. The output of SAP2000 structure analysis can be UCR, deflection, internal force, and placement reactions. The results of the dock structure modeling analysis will be used for subsequent dock designs, the inner force of the dock will be used for the design of dock structure elements such as beams, plates and pile caps, whereas the placement reaction will be used for soil bearing capacity analysis to determine the depth of the stake. The result of this Final Project is dock design with OCDI and BS standard and comparison of dimension, element geometry, model result, reinforcement design and soil bearing capacity analysis from both docks.